Pengaruh Harga, Lokasi, Keragaman Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian Produk Batik di CV Ningrat Prasojo Kediri - Akmelia Lely Susanti (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research aims to determine the influence of the variables price (X1), location (X2), product diversity (X3) on purchasing decisions (Y) for Batik Products at CV Ningrat Prasojo Kediri. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the accidental sampling method, the number of samples in the research was 95 respondents at CV Ningrat Prasojo Kediri. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= -2.240 + 0.193X1 + 0.206X2 + 0.425X3 and the t test results of the price variable had a partially significant effect on purchasing decisions with a sig result of 0.025 < 0.05. Location has a partially significant effect on purchasing decisions, with a sig. 0.011 > 0.05. Product diversity has a partially significant effect on purchasing decisions, with the result being a sig. 0.000 > 0.05. Service quality has a partially significant effect on purchasing decisions, with a sig. 0.000 > 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that price, location, product diversity and service quality simultaneously and significantly influence purchasing decisions at CV Ningrat Prasojo.